Morocco : First Review Under the Arrangement Under the Precautionary And Liquidity Line. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Morocco's First Review Under the Arrangement Under the Precautionary and Liquidity Line (PLL). Significant progress was made in implementing the reform agenda. The program remains broadly on track, and Morocco continues to meet the qualification criteria for a PLL. The fiscal end-September indicative target was missed by 0.7 percent of GDP. Subject to the Executive Board's positive assessment in the context of the 2014 Article IV consultation, the IMF staff recommends the completion of the first review under the PLL arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet